Comparison of the Effects of Topical Ketamine and Tramadol on Postoperative Pain After Mandibular Molar Extraction - GARİP, HASAN; GÖNÜL, ONUR (W B SAUNDERS CO-ELSEVIER INC, 2015)
Purpose: This study compared the analgesic efficacy of postoperative tramadol versus ketamine for preventing pain after mandibular molar extraction. Patients and Methods: Ninety patients who had undergone molar extraction were randomly divided into 3 groups: group T (tramadol 1 mg/kg), group K (ketamine 0.5 mg/kg), and group P (saline 2 mL). The treatment was applied to the extraction sockets using resorbable gelatin sponges. Pain after extraction was evaluated using a visual analog scale (VAS) 0.5, 1, 2, 4, 6, 12, 24, and 48 hours postoperatively. Results: The VAS scores after extraction were statistically higher in group P than in either treatment group. Group K had the lowest pain intensity. Conclusion: This study shows that topical tramadol and ketamine are effective alternatives for decreasing pain after molar extractions.(C) 2015 American Association of Oral and Maxillofacial Surgeons
Keywords: 3RD MOLARS; TONSILLECTOMY